2017
DOI: 10.1039/c7ta01614j
|View full text |Cite|
|
Sign up to set email alerts
|

High surface area, amorphous titania with reactive Ti3+ through a photo-assisted synthesis method for photocatalytic H2 generation

Abstract: A facile approach for the preparation of high surface area, Ti3+ containing titania with good activity for photocatalytic H2 production is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 73 publications
(84 reference statements)
4
68
0
Order By: Relevance
“…This phenomenon has also been reported in various works on disordered or colloidal morphologies . When annealed in air the color of TiO 2 changed to pale yellow that could be explained by a decrease in the amount of defects and the crystallization process.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…This phenomenon has also been reported in various works on disordered or colloidal morphologies . When annealed in air the color of TiO 2 changed to pale yellow that could be explained by a decrease in the amount of defects and the crystallization process.…”
Section: Resultsmentioning
confidence: 84%
“…Several studies have shown that amorphous or disordered TiO 2 ‐based nanomaterials can have the higher photocatalytic activity than crystalline ones, which can be due to larger amounts of absorbed surface water species at the active sites, manifested by the higher concentrations of Ti 3+ at the surface upon band gap illumination . However, as shown in the work, amorphous TiO 2 photocatalysts are not “intrinsically” better than the commercially available crystalline counterparts that may be attributed to the increased recombination of photogenerated carriers. Thereby, understanding the role of TiO 2 crystallinity in the enhancement of the photocatalytic activity is within the scope of many studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons can be explained in detail as follows: (i) the sample HBTF had a larger specific surface area compared with OTF and P25. As is well known, nanomaterials with larger specific surface areas could offer more active sites and absorb more reactant, which leads to a higher photocatalytic performance . (ii) The hierarchically branched structures could improve the photon utilization efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…The use of amorphous materials as catalysts could be one of the approaches to lower the costs of AOPs. As temperature treatment for the crystallization is not required, the synthesis costs are lower, so the preparation procedure is more appropriate to be adopted for large-scale production [25,26]. In general, it is commonly accepted that for effective separation and generation of charge, carrier materials with high crystallinity are required.…”
Section: Introductionmentioning
confidence: 99%